The Relationship Between Self-Concept and Career Choice Maturity of Students Based on Gender - Annisa Puteri Iriani; Akhmad Harum; Abdul Saman (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
This study examines the relationship between students' self-concept and career maturity in terms of gender factors in which aspects of one's role, behaviour, expression and identity and the influence of self-concept components on career choice maturity are linked. This study uses quantitative research with a correlational type. The population of this study was class XII students with a sample of 100 students (50 female students and 50 male students) using Cluster Random Sampling as a sample. Data collection techniques used the self-concept scale from Rogers' theory and career choice maturity from Donald E. Super's career theory. Data analysis used descriptive analysis, product moment correlation analysis, and analysis of linear regression equations. The results showed that the self-concept of female and male students knew their self-concept, including perceptions of physical appearance and behaviour, behaviour based on goals, inspiration and values to be achieved, assessment of achievement according to the ideal self, ability to behave according to the environment, ability to master, respect for oneself, likewise, with the career choice maturity of female students and male students who are in the high category. Based on the correlation test results on variable X (Self-Concept) and Y (Career Choice Maturity) variables of female and male students, it can be concluded that there is a relationship between self-concept and career choice maturity of females 0.68% higher than male students. The self-concept component influences the maturity of career choices for both female and male students. The findings in this study are the effect of the self-concept component on the career choice maturity of female students 2.3% higher than male students, where female students are influenced by self-image and self-identity. In contrast, male students are influenced by their ideal self and self-esteem.